Positive impact of a pre-school-based nutritional intervention on children's fruit and vegetable intake: results of a cluster-randomized trial - Bock, Freia de; Breitenstein, Luise; Fischer, Joachim E. (Public health nutrition, 2012)
Objective: To assess the short-term impact of a nutritional intervention aimed at reducing childhood overweight in German pre-school children. Design: Using a cluster-randomized study design with waiting-list controls, we tested a 6-month intervention administered once weekly by a nutrition expert consisting of joint meal preparation and activities for children and parents such as tasting and preparing nutritious, fresh foods. At baseline, 6 and 12 months, a parent-completed questionnaire assessed fruit and vegetable intakes (primary outcomes) and water and sugared drinks consumption (secondary outcomes). Direct measurement assessed BMI, skinfold thickness and waist-to-height-ratio. An intention-to-treat analysis used random-effects panel regression models to assess the intervention effect, adjusted for each child’s age, gender, immigrant background and maternal education. Setting: Eighteen pre-schools from three south German regions. Subjects: Healthy children aged 3-6 years. Results: Three hundred and seventy-seven (80 %) eligible pre-school children participated in the study. Of these, 348 provided sufﬁcient data for analysis. The sample mean age was 4?26 (SD 0?78) years; the majority (53?2 %) were boys. Children’s fruit and vegetable intakes increased signiﬁcantly (P , 0?001 and P , 0?05, respectively); no signiﬁcant changes in the consumption of water, sugared drinks or anthropometric measurements were noted.Conclusions: Nutritional interventions in pre-schools have the potential to change eating behaviours in young children, which in the long term might reduce risk for developing overweight.